Fernando de Azevedo: from physical education to social sciences - Piletti, Nelson (Revista do Instituto de Estudos Brasileiros, 1994)
This article presents a panoramic view of the life and works of Fernando de Azevedo, concentrating on the following aspects: the man and his work, the specilist in physical education, the literary critic, the educational reformer, the social scientist, his education and society.